Apigenin Attenuates Acetaminophen-Induced Hepatotoxicity by Activating AMP-Activated Protein Kinase/Carnitine Palmitoyltransferase I Pathway - Jiaqi Zhang; Xiaoqiang Liang; Jiacheng Li; Hao Yin; Fangchen Liu; Cheng Hu; Ling Li (Frontiers Media S.A., 2020)
Overuse of acetaminophen (APAP) is a major cause of drug-induced liver failure at the clinics. Apigenin (API) is a natural flavonoid derived from Matricaria chamomilla. The aim of the present study was to investigate the amelioration function of API in APAP-induced hepatotoxicity both in vitro and in vivo and investigate its potential mechanisms. Analysis results of the activities of serum alanine and aspartate aminotransferases (ALT and AST), malondialdehyde, myeloperoxidase (MPO), and reactive oxygen species (ROS) demonstrated therapeutic effects of API. MTT assay results revealed that API attenuated APAP and its metabolic product, N-acetyl-p-benzoquinone imine (NAPQI) induced cytotoxicity in a dose-dependent manner in human liver cells, L-02 cells. Subsequently, metabolomic results of cells and serum analyses demonstrated an aberrant level of carnitine palmitoyltransferase I (CPT1A). We established that API stimulated CPT1A activity in mice liver tissues and L-02 cells. Molecular docking analyses revealed potential interaction of API with CPT1A. Further investigation of the role of CPT1A in L0-2 cells revealed that API reversed cytotoxicity via the AMP-activated protein kinase (AMPK)/GSK-3β signaling pathway and compound C, which is a selective AMPK inhibitor, inhibited activation of CPT1A induced by API. API was bound to the catalytic region of AMPK as indicated by molecular docking results. In addition, compound C suppressed nuclear translocation of nuclear factor erythroid 2-related factor 2 (NRF2) that is enhanced by API and inhibited the antioxidative function of API. In summary, the study demonstrates that API attenuates APAP-induced hepatotoxicity by activating the AMPK/GSK-3β signaling pathway, which subsequently promotes CPT1A activity and activates the NRF2 antioxidant pathway.